Talent Management and The Journey Towards Gender Equality and Women’s Empowerment In South Korea - Yurdagul, Esin (WILAYAH: The International Journal of East Asian Studies, 2020)
Lack of gender equality affects talent management. The journey towards gender equality can be achieved through diversity, inclusion, and empowerment which is a continuous process, according to the International Labour Organization. This paper examines the importance and significance of achieving gender equality in South Korea through diversity, inclusion, and empowerment in public as well as private sector organisations which are shaped by a strict form of Confucianism. The impact of this on talent management in the country is then assessed.